Experimental evidence of the genetic hypothesis on the etiology of bicuspid aortic valve aortopathy in the hamster model - Soto-Navarrete, María Teresa; Pozo-Vilumbrales, Bárbara; López-Unzu, Miguel Ángel; Rueda-Martínez, Carmen; Fernández, M. Carmen; Durán, Ana Carmen; Pavón-Morón, Francisco Javier; Rodríguez-Capitán, Jorge; Fernández, Borja (Frontiers in Cardiovascular Medicine, 2022)
Bicuspid aortopathy occurs in approximately 50% of patients with bicuspid aortic valve (BAV), the most prevalent congenital cardiac malformation. Although different molecular players and etiological factors (genetic and hemodynamic) have been suggested to be involved in aortopathy predisposition and progression, clear etiophysiopathological mechanisms of disease are still missing. The isogenic (genetically uniform) hamster (T) strain shows 40% incidence of BAV, but aortic dilatations have not been detected in this model. We have performed comparative anatomical, histological and molecular analyses of the ascending aorta of animals with tricuspid aortic valve (TAV) and BAV from the T strain (TTAV and TBAV, respectively) and with TAV from a control strain (HTAV). Aortic diameter, smooth muscle apoptosis, elastic waviness and Tgfβ and Fbn2 expression were significantly increased in T strain animals, regardless of the valve morphology. Strain and aortic valve morphology did not affect Mmp9 expression, whereas Mmp2 transcripts were reduced in BAV animals. eNOS protein amount decreased in both TBAV and TTAV compared to HTAV animals. Thus, histomorphological and molecular alterations of the ascending aorta appear in a genetically uniform spontaneous hamster model irrespective of the aortic valve morphology. This is a direct experimental evidence supporting the genetic association between BAV and aortic dilatation. This model may represent a population of patients with predisposition to BAV aortopathy, in which increased expression of Tgfβ and Fbn2 alters elastic lamellae structure and induces cell apoptosis mediated by eNOS. Patients either with TAV or BAV with the same genetic defect may show the same risk to develop bicuspid aortopathy.